The Impact of Implementing Digital Marketing in Public Administration on The Quality of Public Services and Public Satisfaction - Syaifuddin, S. (Golden Ratio of Social Science and Education, 2025)
This study aims to analyze the impact of digital marketing implementation in public administration on the quality of public services and public satisfaction. The research employs a qualitative approach using case studies of government agencies that have integrated digital technology into their public services. Data collection methods include in-depth interviews, documentation studies, and statistical data analysis related to digital platform usage and public interactions.The findings indicate that digital marketing—encompassing social media, web-based applications, and data-driven marketing—plays a pivotal role in enhancing transparency, improving service efficiency, and strengthening interactions between government and society. Despite challenges such as limited infrastructure and low levels of digital literacy, the application of digital marketing has demonstrated a significant positive impact on public satisfaction with public services.This research offers important implications for the formulation of digitalization policies in public administration and provides a valuable contribution to the literature on digital marketing in the public sector.